2000
DOI: 10.1021/bi0010930
|View full text |Cite
|
Sign up to set email alerts
|

Structures of the Contryphan Family of Cyclic Peptides. Role of Electrostatic Interactions in cis−trans Isomerism,

Abstract: The contryphan family of cyclic peptides, isolated recently from various species of cone shell, has the conserved sequence motif NH(3)(+)-X(1)COD-WX(5)PWC-NH(2), where X(1) is either Gly or absent, O is 4-trans-hydroxyproline, and X(5) is Glu, Asp, or Gln. The solution structures described herein of two new naturally occurring contryphan sequences, contryphan-Sm and des[Gly1]-contryphan-R, are similar to those of contryphan-R, the structure of which has been determined recently [Pallaghy et al. (1999) Biochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 20 publications
2
33
0
Order By: Relevance
“…These results are similar to the random coil chemical shift deviations reported for contryphan-R at 5°C and pH 5.8 (7). These results suggest that in the absence of calcium, synthetic glacontryphan-M expresses the highly constrained, disulfidebridged, contryphan loop, which has been observed in previous NMR studies of contryphans-R, Sm, and Vn (5,7,10).…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…These results are similar to the random coil chemical shift deviations reported for contryphan-R at 5°C and pH 5.8 (7). These results suggest that in the absence of calcium, synthetic glacontryphan-M expresses the highly constrained, disulfidebridged, contryphan loop, which has been observed in previous NMR studies of contryphans-R, Sm, and Vn (5,7,10).…”
Section: Resultssupporting
confidence: 77%
“…Contryphans characterized to date are a mixture of two conformers in solution due to cis-trans isomerization of the N-terminal Cys-Pro peptide bond (5). In contrast to previous structure/function studies of contryphan-Sm in which the cis-trans ratio of the Cys-Pro peptide bond was shown to be dependent on stabilizing electrostatic interactions between an N-terminal glycine residue and a glutamine that is positioned between D-Trp and Pro 9 (5), we observed no isomerization in glacontryphan-M in the absence or presence of calcium.…”
Section: Structures Of Metal-free and Calcium-bound Glacontryphan-mmentioning
confidence: 99%
See 1 more Smart Citation
“…All spectra were acquired at 5°C to slow the peptide tumbling and to favour the lowest-energy conformations. 34,35 A discussion of the estimation of backbone structural characteristics from secondary chemical shifts and NOE patterns can be found in the Supplementary Material. NOE volumes were measured using Sparky 36 and referenced internally to fixed distances (pairs of H β s, Gly H α s, Trp ring neighbours) through the ISPA approximation, 37 with an added margin of 0.5 Å to account for uncertainties.…”
Section: Nmr Spectroscopymentioning
confidence: 99%
“…For example, AGP21 has a unique N-terminal sequence ATVEA that was found in five fractions, A7 to A11 (Table I). This is likely because of cis-trans isomerization of Hyp that can lead to temperature-sensitive conformation changes that result in different retention times on RP-HPLC (40,41).…”
Section: Purification and Separation Of Ag-peptides-mentioning
confidence: 99%